The teacher facing diversity: importance of inclusion in early childhood education - Sánchez Serrano, Cinthia Jessica (2026)
Currently, the growing diversity in classrooms demands inclusive pedagogical responses in which the teacher’s role is fundamental, especially in early childhood education. The purpose of this article is to analyze how teachers at this level recognize diversity and how they contribute to creating spaces and developing inclusive individuals. The research was conducted with a qualitative approach, employing phenomenology to understand the experiences of teachers at a preschool in Mexico City. A semi-structured interview was conducted with these teachers, allowing us to explore their perceptions, practices, challenges, and struggles in the face of student diversity. The analysis of the data revealed the teachers' conceptions, tensions, and strategies in their daily practice. The findings underscore that early childhood education is a strategic space for consolidating equity and equality, as the foundations for recognizing diversity and respectful coexistence are laid at this stage. The importance of initial teacher training is highlighted, and it is concluded that early childhood teachers are key agents in promoting a more just and inclusive school from the earliest stages.